Denasalisation in the spoken french of ijebu undergraduate french learners in selected universities in south west of Nigeria (2018)
Denasalisation is a lexical phenomenon brought into play during the process of lexicalisation while nasalisation is a natural process which occurs when an oral sound is modified in the environment of an adjacent nasal sound. Little attention is paid to the former because phonologists admit that nasalisation is more natural during speech production. This paper, therefore, examined denasalisation in the spoken French of 50 Ijebu Undergraduate French Learners (IUFLs) in Selected Universities in South West of Nigeria with a view to establishing instances of denasalisation in their spoken French. Data collection for this study was through tape-recording of participants’ production of 30 sentences containing French vowel and consonant sounds. Goldsmith’s Autosegmental phonology blended with distinctive feature theory was used to analyse instances of denasalisation in the data collected. The study revealed instances of denasalisation of nasal sounds at initial and final positions in the spoken French of the IUFLs.